A multiple emulsion composition and a method of producing the emulsion - Basri, Mahiran; Teo, Brian Sheng Xian; Abdul Malik, Emilia; Tejo, Bimo Ario (2013)
A multiple emulsions system comprises an aqueous continuous phase configured to carry a hydrophilic first active agent; liquefied fluorocarbon droplets, dispersed within the continuous phase, solubilizing a third active agent; and an oil phase, carrying a second active agent, enveloped onto the fluorocarbon droplets to substantially shield the fluorocarbon off the continuous phase forming three immiscible liquid phases thereof; wherein the first, the second and the third active agents are different.